2012
DOI: 10.1186/1471-2474-13-89
|View full text |Cite
|
Sign up to set email alerts
|

Sutures versus staples for wound closure in orthopaedic surgery: a randomized controlled trial

Abstract: BackgroundA recently published meta-analysis comparing metallic staples to sutures in orthopaedic procedures revealed three fold increase in risk for infection in stapled wounds. The studies included in the meta-analysis are at risk of bias due to experimental design limitations. A large randomized controlled trial is proposed to direct orthopaedic surgeons in their choice of wound closure material.Methods/DesignA parallel group randomized controlled trial with institutional review board approval will be condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…Many studies have previously compared wound closure techniques in TKA [2,3,6,[15][16][17][18]. Results have been highly variable and currently there is no consensus on a superior closure method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have previously compared wound closure techniques in TKA [2,3,6,[15][16][17][18]. Results have been highly variable and currently there is no consensus on a superior closure method.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have compared different closure techniques in TKA [2,3,6,[15][16][17][18]. From the perspective of wound complications, one recent meta-analysis by Smith et al showed that staple closure resulted in increased rates of infection after both hip and knee arthroplasty in comparison to running subcuticular [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the reviewed articles echoed the fact that stapling of wound was quicker and time saving when compared to conventional wound/skin closure methods. [4][5][6][7][8][9][10][11][12][13] The mean time saving of 80% was possible with stapling devices and was 2.7 times faster than conventional methods. 6,11 Most of the articles reviewed were also having an overall similar view when comparing the cost of using staples against conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…There was an overall agreement in the fact that staples were associated with more pain and discomfort to patients. 7,9,10,16 A meta-analysis which compared most of randomized control trials made a strong statement in need to incorporate more objective methods for assessment of cosmetic and patient satisfaction in further studies. 10 Except the fact that staples were faster, costlier and painful, none of the other factors compared here below have a clear consensus and the views of one group of study differed significantly from the other beyond comparison.…”
Section: Discussionmentioning
confidence: 99%